Kualitas Pelayanan Publik Dalam Penyelenggaraan Program Dana Pensiun Pada PT. Taspen (Persero) Cabang Kendari - Kambolong, Makmur; Mustakim, Mustakim; Hidayat, Dinul (REZ PUBLICA, 2021)
Â This study aims to determine the quality of public services in administering the pension fund program at PT. TASPEN (Persero) Branch Kendari. The method used in this research is descriptive qualitative research with data collection techniques using observation, interview and documentation techniques. The results of this study indicate that the quality of public services in administering the pension fund program at PT. TASPEN (Persero) Branch Kendari is quite good, this can be seen from the results of the research which refers to the five dimensions of service quality which include tangible, reliability, responsiveness, assurance and empathy for the two types of Civil Servant pension fund programs at PT. TASPEN (Persero) Branch Kendari namely Old Age Savings and Pension Program. Even so, there are still shortcomings that need to be fixed, namely the completion of the claim process for Old Age Savings funds and pension salary payments that cannot be completed on time, irregular parking lots and lack of facilities for participant families who come to take them.Â